2020
DOI: 10.1371/journal.pone.0241784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term methylene blue treatment on the composition of mouse gut microbiome and its relationship with the cognitive abilities of mice

Abstract: In recent years, methylene blue (MB) has attracted considerable interest as a potential drug for the treatment of methemoglobinemia and neurodegenerative diseases. MB is active against microorganisms from various taxonomic groups. However, no studies have yet been conducted on the effect of MB on the intestinal microbiome of model animals. The aim of this work was to study the effect of different concentrations of MB on the mouse gut microbiome and its relationship with the cognitive abilities of mice. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
(63 reference statements)
0
10
1
1
Order By: Relevance
“…Gut microbiome of MB-treated mice contained 11 genera with OTU of more than 0.02, while the control mice and RSV-treated mice contained 17 genera and DMF-treated mice contained 16 genera (Figure 11). Thus, these results and our previous data [27] show some evidence of MB-induced dysbiosis, but we cannot say that MB causes dysbiosis, since the other markers of dysbiosis are not observed. It is known that dysbiosis altered brain function and induced depressive-like behavior [86].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Gut microbiome of MB-treated mice contained 11 genera with OTU of more than 0.02, while the control mice and RSV-treated mice contained 17 genera and DMF-treated mice contained 16 genera (Figure 11). Thus, these results and our previous data [27] show some evidence of MB-induced dysbiosis, but we cannot say that MB causes dysbiosis, since the other markers of dysbiosis are not observed. It is known that dysbiosis altered brain function and induced depressive-like behavior [86].…”
Section: Discussioncontrasting
confidence: 54%
“…This implies the long-term treatment by drugs that are aimed at slowing down the processes of cognitive impairment, which can increase the degree of the effect of the drug on the intestinal composition of the microbiome. Recently, we found that treatment by a high concentration of MB (50 mg/kg/day) during one month induced dysbiosis, which manifested in an increase in Proteobacteria level [ 27 ]. Classically thought to be markers of dysbiosis in inflammatory bowel disease are increase in the Proteobacteria and Bacteroidetes phyla bacteria, decrease in the number of Firmicutes phylum bacteria, and decrease in the alpha-diversity index [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteroidales, Bacteroidia, Tannerellaceae, and Actinobacteria were the more enriched taxonomy after FMT. These genera were reported to be associated with cognitive function (Figure 2(C)) [14][15][16] . Functional biomarker analysis using the Kruskal-Wallis H test was performed between the pre-and post-FMT groups by using EzBio-Cloud Apps (ChunLab Inc., Seoul, Korea).…”
Section: Discussionmentioning
confidence: 96%
“…Phenothiazine analogs have versatile applications across many diseases, including antimicrobial effects [ 24 , 25 , 26 ], antitumor effects [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and potential roles in the treatment of neurodegenerative disease [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In the past, we showed PMZ binds to Abeta available in the brain lysate of 5XFAD mice in an in vitro study.…”
Section: Resultsmentioning
confidence: 99%